Analisis Performa Heater Pada Unit Heat Transfer Medium di Polymer Plant dengan Produk Sumber Pemanas - Puput Ayu Wulandari, Puput; Hilman Imadul Umam, Hilman; Aurelius Airlangga Suryo Wicaksono, Aurelius (Jurnal Serambi Engineering, 2025)
One of the main requirements in polymer processing is heat. A fired heater is used in the Heat Transfer Medium unit to obtain heat. The efficiency, heat loss, and specific consumption of fired heaters greatly impact the efficiency of energy use in processing. According to SNI, to maintain the efficiency of the fired heater, it is necessary to periodically review its performance using direct and walkthrough methods. The analysis results from three consecutive days showed an efficiency of 87%, 89%, and 89%. The heat loss was 13%, 11%, and 11%. The specific consumption was 70.66, 72.65, and 72.69 Nm³/ton. Overall, these values meet SNI standards: 92% efficiency, 10-15% heat loss, and ≥74 Nm³/ton specific consumption. However, to maintain or increase the efficiency value, it is necessary to monitor operating conditions and conduct regular periodic checks to prevent system leaks that increase heat loss and reduce efficiency.